Impossible creatures eaudiobook - Rundell, Katherine (Impossible Creatures, 2024)
#1 NEW YORK TIMES BESTSELLER • Two kids race to save the world’s last magical place in the first book of a landmark new fantasy series, from “a writer with an utterly distinctive voice and a wild imagination.” (Philip Pullman, author of The Golden Compass ) “An instant classic from one of the most gifted storytellers of our time, Impossible Creatures is an astonishing miracle of a book.” —Katherine Applegate, Newbery Medal Winner for The One and Only Ivan A WALL STREET JOURNAL BEST CHILDREN'S BOOK OF THE YEAR • A PUBLISHERS WEEKLY, KIRKUS REVIEWS, AND SHELF AWARENESS BEST BOOK OF THE YEAR The day that Christopher saved a drowning baby griffin from a hidden lake would change his life forever. It’s the day he learned about the Archipelago—a cluster of unmapped islands where magical creatures of every kind have thrived for thousands of years, until now. And it’s the day he met Mal—a girl on the run, in desperate need of his help. Mal and Christopher embark on a wild adventure, racing from island to island, searching for someone who can explain why the magic is fading and why magical creatures are suddenly dying. They consult sphinxes, battle kraken, and negotiate with dragons. But the closer they get to the dark truth of what’s happening, the clearer it becomes: no one else can fix this. If the Archipelago is to be saved, Mal and Christopher will have to do it themselves. Katherine Rundell’s story crackles and roars with energy and delight. It is brought vividly to life with more than 60 illustrations, including a map and a bestiary of magical creatures. This audiobook edition includes a downloadable Bestiary PDF to accompany the audio, as well as drawings for each beast.